2020
DOI: 10.1038/s41467-020-20144-w
|View full text |Cite
|
Sign up to set email alerts
|

HIF1A signaling selectively supports proliferation of breast cancer in the brain

Abstract: Blood-borne metastasis to the brain is a major complication of breast cancer, but cellular pathways that enable cancer cells to selectively grow in the brain microenvironment are poorly understood. We find that cultured circulating tumor cells (CTCs), derived from blood samples of women with advanced breast cancer and directly inoculated into the mouse frontal lobe, exhibit striking differences in proliferative potential in the brain. Derivative cell lines generated by serial intracranial injections acquire se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 52 publications
0
37
0
Order By: Relevance
“…In addition to the increased PSPC1 expression in the monocytes of patients with OSA regulated by HIF1α transcriptional pathways, the high circulating PSPC1 levels found in these patients could contribute to a paracrine effect. Furthermore, it has been reported that hypoxia, by HIF1α, induces MMP2 expression in endothelial cells, cardiac fibroblasts, macrophages, and breast cancer cells [37][38][39][40]. Hypoxia also promoted TGFβ1/Smad signaling via HIF1α [41].…”
Section: Discussionmentioning
confidence: 98%
“…In addition to the increased PSPC1 expression in the monocytes of patients with OSA regulated by HIF1α transcriptional pathways, the high circulating PSPC1 levels found in these patients could contribute to a paracrine effect. Furthermore, it has been reported that hypoxia, by HIF1α, induces MMP2 expression in endothelial cells, cardiac fibroblasts, macrophages, and breast cancer cells [37][38][39][40]. Hypoxia also promoted TGFβ1/Smad signaling via HIF1α [41].…”
Section: Discussionmentioning
confidence: 98%
“…These differences in hypoxia signaling may be maintained in CTCs after dissemination and intravasation via epigenetic mechanisms (38). This may explain why differences in hypoxia signaling have been shown to contribute to metastatic ability of clustered CTCs (39) and microenvironment-dependent organ-specific metastasis (40). Intriguingly, the majority of clustered CTCs from breast tumors show up-regulated hypoxia signaling (39).…”
Section: Discussionmentioning
confidence: 99%
“…HIF1a up-regulates a number of genes that support tumor cells to adopt to the hypoxic microenvironment (5). HIF1a overexpression has been detected in solid tumors and is associated with the progression of a variety of cancers, including ovarian cancer (6), breast cancer (7), non-small cell lung cancer (8) and pancreatic cancer (9). Studies have shown that HIF1a affects the regulation of tumor cell proliferation, angiogenesis, apoptosis and chemotherapy resistance during tumor development (10).…”
Section: Discussionmentioning
confidence: 99%